Phosphorylation of the Bin, Amphiphysin, and RSV161/167 (BAR) domain of ACAP4 regulates membrane tubulation - Zhao, Xuannv (National Academy of Sciences, 2013)
ArfGAP With Coiled-Coil, Ankyrin Repeat And PH Domains 4 (ACAP4) is an ADP-ribosylation factor 6 (ARF6) GTPase-activating protein essential for EGF-elicited cell migration. However, how ACAP4 regulates membrane dynamics and curvature in response to EGF stimulation is unknown. Here, we show that phosphorylation of the N-terminal region of ACAP4, named the Bin, Amphiphysin, and RSV161/167 (BAR) domain, at Tyr34 is necessary for EGF-elicited membrane remodeling. Domain structure analysis demonstrates that the BAR domain regulates membrane curvature. EGF stimulation of cells causes phosphorylation of ACAP4 at Tyr34, which subsequently promotes ACAP4 homodimer curvature. The phospho-mimicking mutant of ACAP4 demonstrates lipid-binding activity and tubulation in vitro, and ARF6 enrichment at the membrane is associated with ruffles of EGF-stimulated cells. Expression of the phospho-mimicking ACAP4 mutant promotes ARF6-dependent cell migration. Thus, the results present a previously undefined mechanism by which EGF-elicited phosphorylation of the BAR domain controls ACAP4 molecular plasticity and plasma membrane dynamics during cell migration.